PROTOCOL: Mutual Help Organizations to Support Recovery Among Individuals Who Use Drugs: A Systematic Review Protocol - Emily A. Hennessy; Brandon G. Bergman; Leonard L. Levin; Jenny O'Connor; Morgan Klein; John F. Kelly (Campbell Systematic Reviews)
ABSTRACT This is the protocol for a Campbell systematic review. The objectives are as follows: (1) What kinds of mutual‐help organizations for drug use disorders have been studied with evidence available in the empirical literature? (2) What is the nature of the evidence with regard to the different types of mutual‐help organizations?—(a) To what extent are these entities shown to help initiate, sustain, and enhance rates of remission from drug use disorders and improve other functional outcomes when the available evidence is subjected to rigorous scientific scrutiny? (b) To what extent do different mutual‐help organizations confer differential benefit and to whom, how, and over what period? (c) To what extent have cost benefit or cost effectiveness studies indicated that these entities are cost‐effective?